Temporal dynamics of mildly deleterious nonsynonymous substitutions in mitochondrial gene sequences in rodents and moles - Suzuki, Hitoshi (Dryad, 2021)
In our previous studies, the evolutionary rate (substitutions/site/million
years) of mitochondrial DNA (mtDNA) in rodents and moles was estimated to
be approximately 0.11 in more recent divergence times of a few tens of
thousands of years and declined quickly to approximately 0.03 in more
distant divergence times. However, the modes and mechanisms associated
with the time dependency have not been well documented. We addressed the
abundance of nonsynonymous substitutions that had appeared in the
protein-coding region of mitochondrial cytochrome b gene
sequences in rodents and moles, using sequences obtained from the
nucleotide database. We collected 23 haplogroups with signals of
late Quaternary population expansion events and categorized them into
three groups. The expansion events were predicted to have started during
the last 15,000 years (Group I), ca. 53,000 years ago (Group II), and
130,000-230,000 years ago (Group III). We counted the numbers of
nonsynonymous and synonymous substitutions in all haplogroups. The
nonsynonymous substitution ratios were exclusively low (0.06–0.20) in
Groups II and III. By contrast, the values in Group I varied markedly, and
Group I could be further classified into two subgroups based on high
(0.28–0.43) and low (0.09–0.20) values of the nonsynonymous substitution
ratio, which were roughly associated with the time expansion started,
suggesting that the shift from high to low values of the nonsynonymous
substitution ratio occurred within the last 15,000 years. The Group II and
III networks exhibited two- or three-step star-shaped structures and a
trend of frequent nonsynonymous substitutions on exterior branches, which
were less frequent on interior branches, supporting the idea that
processing to remove nonsynonymous substitutions occurs over a short
evolutionary time.  Based on temporal dynamics, nonsynonymous
mtDNA substitutions in small mammals accounted for 40% of all
substitutions during the very early evolutionary stage and then rapidly
declined, dropping to approximately 15%. This process appears to have been
completed in ca. 15,000 years. This is a good explanation of the
time-dependent trend in the rate of mtDNA evolution predicted by previous
studies.